2018
DOI: 10.1111/dme.13675
|View full text |Cite
|
Sign up to set email alerts
|

Management of hyperglycaemia and steroid (glucocorticoid) therapy: a guideline from the Joint British Diabetes Societies (JBDS) for Inpatient Care group

Abstract: Glucocorticoids (steroids) are widely used across many medical specialities for their anti-inflammatory and immunosuppressive properties. However, one of their major side effects is the development of hyperglycaemia. It is well recognized that high glucose levels in people with diabetes in hospital are associated with harm and increased lengths of hospital stay. The use of glucocorticoid (steroid) treatment in people with pre-existing diabetes will undoubtedly result in worsening glucose control, and this may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
134
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(147 citation statements)
references
References 11 publications
1
134
0
12
Order By: Relevance
“…However, the guidelines stated that oral antidiabetic like glicazide and metformin may be administered gradually to maximum dose (320 mg for glicazide and 2000 mg for metformin daily). 20 Diabetes has a role in causing delayed wound healing due to many complex pathophysiology and mechanisms. Wound in diabetic patients is accompanied with hypoxia due to lack of tissue perfusions or angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the guidelines stated that oral antidiabetic like glicazide and metformin may be administered gradually to maximum dose (320 mg for glicazide and 2000 mg for metformin daily). 20 Diabetes has a role in causing delayed wound healing due to many complex pathophysiology and mechanisms. Wound in diabetic patients is accompanied with hypoxia due to lack of tissue perfusions or angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient management of type 1 diabetes and ketoacidosis [114,[152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170] General Admitting institutions and hospitals should make provisions to allow adults with type 1 diabetes to diabetes self-manage if they are well enough to do so.…”
Section: Categorymentioning
confidence: 99%
“…Evidence indicates that above 10% inpatients need steroid for variety disease [1], with the treatment duration vary from less than 5 days to > 5 years [2]. An impairment of glycemic metabolism or even steroid-induced diabetes may occur in subjects with normal glucose tolerate [3]. Although a pilot study observed that the use of high-dose dexamethasone may not lead to glucocorticoid-induced diabetes [4].…”
Section: Introductionmentioning
confidence: 99%